Percutaneous transhepatic biliary drainage may be the preferred preoperative drainage method in hilar cholangiocarcinoma - Ba, Yongjiang; Yue, Ping; Leung, Joseph W.; Wang, Haiping; Lin, Yanyan; Bai, Bing; Zhu, Xiaoliang; Zhang, Lei; Zhu, Kexiang; Wang, Wenhui; Meng, Wenbo; Zhou, Wence; Liu, Ying; Li, Xun (Endoscopy International Open, 2020)
Background and study aims Preoperative biliary drainage of hilar cholangiocarcinoma (HC) is controversial. The goal of this study was to compare the clinical outcome and associated complications for types II, III, and IV HC managed by percutaneous transhepatic biliary drainage (PTBD) and endoscopic retrograde cholangiopancreatography (ERCP).Patients and methods Between January 2011 and June 2017, a total of 180 patients with II, III, and IV HC were enrolled in this retrospective cohort study. According to the drainage method, patients were divided into two groups: PTBD (n = 81) and ERCP (n = 99). This study was registered with ClinicalTrials.gov, NCT03104582, and was completed.Results Compared with the PTBD group, the ERCP group had a higher incidence of post-procedural cholangitis (37 [37.37 %] vs. 18 [22.22 %], P = 0.028) and pancreatitis (17 [17.17 %] vs. 2 [2.47 %], P = 0.001); required more salvaged biliary drainage (18 [18.18 %] vs. 5 [6.17 %], P  = 0.029), and incurred a higher cost (P < 0.05). Patients with type III and IV HC in the ERCP group had more cholangitis than those in the PTBD group (26 [36.62 %] vs. 11 [18.03 %], P = 0.018). The rate of cholangitis in patients who received endoscopic bilateral biliary stents insertion was higher than patients with unilateral stenting (23 [50.00 %] vs. 9 [26.47 %], P = 0.034), and underwent PTBD internal-external drainage had a higher incidence of cholangitis than those with only external drainage (11 [34.36 %] vs. 7 [14.29 %], P = 0.034). No significant difference in the rate of cholangitis was observed between the endoscopic unilateral stenting group and the endoscopic nasobiliary drainage group (9 [26.47 %] vs. 5 [26.32 %], P = 0.990). Conclusion Compared to ERCP, PTBD reduced the rate of cholangitis, pancreatitis, salvage biliary drainage, and decreased hospitalization costs in patients with types II, III, and IV HC. Risk of cholangitis for patients with types III and IV was significantly lower in the PTBD group.